Local wisdom and Stakeholder engagement for corporate social responsibility (CSR) initiatives in Indonesia - Rosilawati, Yeni; Ahmad, Jamilah (Opción, 2019)
This paper explores the implementation of Corporate Social Responsibility (CSR) initiatives of Aqua Bali Company through the engagement of stakeholders and local wisdom in the effort to conserve the Ayung river, the longest river on the island of Bali. The qualitative software QSR-NVivo 11 was used to clean the data, code and analyze the data sets. Result also indicates that the involvement of stakeholders in developing trust and long term relationships between company and stakeholders is making the project a success. In conclusion, the CSR of Aqua Bali is deeply rooted in the commitment of the organization.